2009
DOI: 10.1083/jcb.200812042
|View full text |Cite
|
Sign up to set email alerts
|

TIP47 functions in the biogenesis of lipid droplets

Abstract: TIP47 (tail-interacting protein of 47 kD) was characterized as a cargo selection device for mannose 6-phosphate receptors (MPRs), directing their transport from endosomes to the trans-Golgi network. In contrast, our current analysis shows that cytosolic TIP47 is not recruited to organelles of the biosynthetic and endocytic pathways. Knockdown of TIP47 expression had no effect on MPR distribution or trafficking and did not affect lysosomal enzyme sorting. Therefore, our data argue against a function of TIP47 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
253
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(272 citation statements)
references
References 51 publications
17
253
1
1
Order By: Relevance
“…By demonstrating that the C-terminal region of ADPH folds independently of the N-terminal region and that it binds liposome membranes, we now have direct evidence that ADPH is composed of two independently functioning domains: an N-terminal domain that targets it to CLD and a C-terminal domain that mediates membrane binding. A similar functional organization of TIP47 has been proposed (39). Although direct evidence of the ability of the C-terminal region of TIP47 to bind membranes has not been demonstrated, it is likely that it also contains membrane binding elements based on the similarity to the ADPH C-terminal sequence and on observations that recombinant full-length TIP47 induces fragmentation of liposomes into discs (39).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By demonstrating that the C-terminal region of ADPH folds independently of the N-terminal region and that it binds liposome membranes, we now have direct evidence that ADPH is composed of two independently functioning domains: an N-terminal domain that targets it to CLD and a C-terminal domain that mediates membrane binding. A similar functional organization of TIP47 has been proposed (39). Although direct evidence of the ability of the C-terminal region of TIP47 to bind membranes has not been demonstrated, it is likely that it also contains membrane binding elements based on the similarity to the ADPH C-terminal sequence and on observations that recombinant full-length TIP47 induces fragmentation of liposomes into discs (39).…”
Section: Discussionmentioning
confidence: 96%
“…A similar functional organization of TIP47 has been proposed (39). Although direct evidence of the ability of the C-terminal region of TIP47 to bind membranes has not been demonstrated, it is likely that it also contains membrane binding elements based on the similarity to the ADPH C-terminal sequence and on observations that recombinant full-length TIP47 induces fragmentation of liposomes into discs (39). The apparent similarities in the structural properties and functional organizations of ADPH and TIP47 raise questions about whether these proteins serve similar physiological roles.…”
Section: Discussionmentioning
confidence: 99%
“…These screens have surprisingly revealed that more than 1% of the genes in eukaryotic genomes are involved in LD biology (3)(4)(5), underscoring the importance of the LD in normal cellular physiology. Several members of the perilipin family, namely plin2, plin3, and plin4, have been implicated as having roles in LD formation (6)(7)(8). However, most evidence supports a role of the plin family in the regulated lipolysis of LDs (9).…”
mentioning
confidence: 92%
“…The Rab9 effector TIP47 binds the cytoplasmic domains of mannose-6-phosphate receptors (MPRs) in a Rab9-GTP-stimulated manner and is required for the return of this cargo to the Golgi complex (Carroll et al 2001). Because TIP47 is also involved in lipid droplet biogenesis under conditions of rapid fat storage, it remains to be determined if TIP47 might be a shared effector that also interacts with one of the myriad of Rab GTPases involved in lipid droplet formation or, alternatively, promotes interorganellar tethering to lipid droplets to allow access to critical lipid regulators of endocytosis Bulankina et al 2009;Hynson et al 2012). Indeed, Tip47 and Rab9 are important targets in viral infectivity and have been associated with lipid droplet consumption, suggesting that resolving this open question will be of significant interest (Murray et al 2005;Chen et al 2009b;Carvalho et al 2012;Vogt et al 2013).…”
Section: Rab Gtpases In Vesicle Buddingmentioning
confidence: 99%